Left pulmonary artery agenesis with pulmonary hypoplasia in an elderly patient: a rare case report - Santra, A; Padhi, R; Dutta, P; Manjhi, R; Pothal, S; Panda, B (Bangladesh Journal of Medical Science, 2013)
Proximal interruption of the unilateral pulmonary artery is a rare congenital anomaly, which is often associated with other cardiovascular abnormalities. It is usually diagnosed in children but rarely discovered in adulthood as an isolated phenomenon, occurring more frequently on the right side and is often associated with a contralateral aortic arch. We are presenting a rare case of a sixty year old male who was diagnosed with left lung hypoplasia due to proximal interruption of left pulmonary artery with left sided aortic arch without any associated cardiovascular anomalies. DOI: http://dx.doi.org/10.3329/bjms.v12i4.13689 Bangladesh Journal of Medical Science Vol. 12 No. 04 October 13 Page 462-466